The spark the 28-day breakthrough plan for losing weight, getting fit, and transforming your life - Downie, Chris (Carlsbad, Calif. : Hay House, 2009)
From the experts who created SparkPeople.com, one of the most successful online weight-loss programs to date, comes The Spark, a ground-breaking book that focuses on what you can do, instead of what you can't do.
The fuel for improvement system -- Cornerstone: focus -- Cornerstone: fitness -- Cornerstone: fire -- Cornerstone: positive force -- The sparkdiet -- Stage 1: fast break -- Stage 2: healthy diet habits -- Stage 3: lifestyle change -- Stage 4: spread the spark.
Includes bibliographical references (p. 225-227).
Description based on print version record.
Keywords: Weight loss; Physical fitness; Health; Electronic books